RANCANG BANGUN PEMANAS AIR TENAGA SURYA TIPE KOTAK SEDERHANA YANG DILENGKAPI PHASE CHANGE MATERIAL DENGAN KAPASITAS 100 LITER AIR - Fauzi Fauzi; Tulus B. Sitorus; Himsar Ambarita (Jurnal Dinamis, 2012)
AbstractSolar water heater used in this study is a type of solar water heater simple boxincorporating phase change material (PCM) with capacity of 100 liters of water, which is used asa shower. In general, research in Indonesia solar water heater does not use heat storagematerial, the use of excess heat storage material of box type solar water heater is, one that canbe used not only to heat water during the day but also at night. So the research is veryinteresting to study because it has use phase change material, heats water indirectly is verypossible. In this paper, will be on the pillowcase on how the use of PCM in the heats waterindirectly. Here also will be reviewed on the design of solar water heater with dimensions oflength 2 m, width 1 m, thickness 0.180 m, 0.250 m high, 2 m2 absorber surface area for acapacity of 100 liters of hot water and the heat generated is lost in the solar water heater perday was 8.36 MJ. PCM used are Stearic Acid (melting point 51.5 ° C). Test site is in the city ofMedan, Indonesia with 40 latitude 980 BT.Keywords: Solar water heater with storage material, PCM.